Venture Capital Financing as A Driver for Entrepreneurship Development in Africa. A Literature Review and Future Research Agenda - Kato Idi Ahmed Idi; Chiloane -Tsoka Evelyn Germinah (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: Several academics and practitioners have observed entrepreneurship development as a critical pillar for the prosperity of high-growth entrepreneurial ventures, new job opportunities, promotion of exports, and improvement of tax revenue across all countries. However, little is known about the role of VC in stimulating entrepreneurship development in Southern and East African regions. Design/methodology/approach: Therefore, we reviewed 121 articles in international accredited journals from 2001 to 2022 to provide insights into this field of study. Findings: Our results show that 90% of the reviewed articles were empirical, and 10% were theoretical. Furthermore, only 7% of the articles support the role of VC investment in entrepreneurship development. Colossal studies present beneficial results on this topic, but they are mainly from developed economies in Latin America and Europe, thus widening the literature gaps in Africa. Research limitations/implications: Whereas the VC industry has received growing attention from emerging economies lately, it is still divided and restricted to technology entrepreneurship sector. Practical implications: To the best of our understanding, this is the first multidisciplinary and integrative analysis that delivers a current thematic overview and insights into the explicit fields to create instincts for further empirical studies on the role of VC investment in entrepreneurship development in developing countries. Second, our literature analysis discloses significant literature gaps. Lastly, the authors improve the current literature by suggesting future research directions centred on an integration of exceeding Venture capital investors’ technological skills to foster entrepreneurship development. Paper type: Research paper